Comparison between two approaches for the transversus abdominis plane block in canine cadavers. (January 2021) - Romano, Marta; Portela, Diego A.; Thomson, Alexander; Otero, Pablo E.
Abstract: Objective: To compare the dye distribution following either two lateral abdominal or one lateral abdominal and one subcostal ultrasound-guided transversus abdominis plane (TAP) injections of a clinically relevant volume of dye solution in dogs. Study design: Randomized cadaveric study. Animals: A total of eight canine cadavers. Methods: On one side of each cadaver, two TAP injections were performed on the lateral aspect of the abdomen (approach LL), caudal to the last rib and cranial to the iliac crest. On the contralateral hemiabdomen, one subcostal (caudal to the costal arch) and one lateral abdominal injection (between last rib and iliac crest), were performed (approach SL). Side allocation was randomly determined. A spinal needle was introduced in-plane to the transducer for each injection of methylene blue (0.25 mL kg −1 ). All cadavers were dissected to assess dye distribution and number of stained target nerves. Results: All injections were performed in the TAP. The proportion of target nerve staining was 53.5% versus 80.4% with approaches LL and SL, respectively ( p  = 0.005). Approach LL stained the first lumbar (L1) spinal nerve in 100% of injections and ninth thoracic (T9), T10, T11, T12, T13 and L2 were stained in 0%, 0%, 37.5%, 62.5%, 87.5% and 87.5% of injections, respectively. Approach SL stained T11, L1 and L2 in 100% of injections and T9, T10, T12 and T13 were stained in 37.5%, 87.5%, 75% and 62.5% of injections, respectively. Approach SL resulted in greater staining of nerves cranial to T12 compared with approach LL. The two approaches were equivalent in staining nerves caudal to T12. Conclusions and clinical relevance: Approach SL provided a broader distribution of the injected solution than approach LL, which may result in a larger blocked area in live animals undergoing celiotomy.